Policing black bodies: how black lives are surveilled and how to work for change - Hattery, Angela (Rowman & Littlefield, 2021)
Setting the stage -- Social protest, or a logical response to policing black bodies -- Mass incarceration -- School-to-prison pipeline -- The prison-industrial complex : the new plantation economy -- Policing black women's bodies -- Policing trans bodies -- Police killings of unarmed black people -- The ultimate failure : exoneration -- Policing black athletes' bodies -- Intersectionality, color-blind racism, and a call to action.